Dark towers [compact disc, unabridged] : Deutsche Bank, Donald Trump, and an epic trail of destruction - Enrich, David, 1979- (Harper Audio, 2020)
"A searing exposé by an award-winning journalist of the most scandalous bank in the world, including its shadowy ties to Donald Trump's business empire"--